Alignment of Performance-Based Financing in Health with the Government Budget : A Principle-Based Approach - Piatti-Fuenfkirchen, Moritz; Hadley, Sierd; Mathivet, Benoit (World Bank, Washington, DC, 2021)
Performance-based financing (PBF) is the transfer of funds to health facilities so they can provide a pre-agreed set of services according to appropriate standards of quality and administration. These initiatives have introduced a wide set of reforms, including in provider autonomy, access to financial services, flexibility on the utilization of funds, a performance orientation on the budget allocation, and rigorous verification protocols. This tends to set PBF apart from the prevailing public financial management (PFM) systems that often remain input-based and thereby create a sustainability challenge. If the prevailing PFM system remains in parallel to the PBF, countries are likely to return to the legacy PFM system once PBF donor resources dry up. This paper unpacks this problem. It develops a conceptual framework about how to think about aligning PBF principles with PFM structures; offers a set of diagnostic questions for an assessment; and helps guide an analyst through the process of developing a reform roadmap, considering country context. The paper also proposes a reform roadmap to be centered around the following four facility financing pillars: (i) provider autonomy, (ii) financial management capacity, (iii) output-oriented budget provisions, and (iv) a unified payment system. As a discussion paper, this work aims to solicit feedback on the proposed approach from the PBF and PFM community.